2022
DOI: 10.1007/s40843-022-2255-2
|View full text |Cite
|
Sign up to set email alerts
|

Anionic surfactant anchoring enables 23.4% efficient and stable perovskite solar cells

Abstract: Nonradiative recombination losses at defects in metal halide perovskite films are responsible for hindering the improvement of the photovoltaic performance and stability of perovskite solar cells (PSCs). Here, we report a feasible multifunctional additive strategy that uses cesium stearate to passivate defects in perovskite films and simultaneously enhances the tolerance to light and moisture stress. Nonradiative recombination losses are effectively suppressed in target films that exhibit improved crystallinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Long-alkyl chain surfactants have been regarded as effective additives to change the rheological properties of the inks and improve the quality of perovskite films. 25,26 In view of their molecular structure, the hydrophobic groups are generally alkyl chains or cycloalkanes containing 8-18 carbon atoms. We have systematically screened the effect of long-chain surfactants according to the number and length of their alkyl chains and concluded that increasing the alkyl-chain length is benign to the performance.…”
Section: Papermentioning
confidence: 99%
“…Long-alkyl chain surfactants have been regarded as effective additives to change the rheological properties of the inks and improve the quality of perovskite films. 25,26 In view of their molecular structure, the hydrophobic groups are generally alkyl chains or cycloalkanes containing 8-18 carbon atoms. We have systematically screened the effect of long-chain surfactants according to the number and length of their alkyl chains and concluded that increasing the alkyl-chain length is benign to the performance.…”
Section: Papermentioning
confidence: 99%
“…Wang et al introduced cesium stearate (CsSt) to passivate both positively and negatively charged defects by carboxylate anions and Cs + cations, respectively, leaving a long alkyl chain outside the surface for further protection against the ambient environment. 88 Zhou et al employed an anionic additive, TDCA, containing two carboxyl and a thiophene, which strengthened the coordination bonds with Pb 2+ due to the donation of electron pairs from S in the thiophene groups. 89 Compared with small molecules, polymers usually possess higher mechanical strength and viscosity in solution, and thus they are much more suitable for large-area device fabrication techniques such as blade or slot-die coating and screen printing.…”
Section: Bulk Defectsmentioning
confidence: 99%
“…Wang et al introduced cesium stearate (CsSt) to passivate both positively and negatively charged defects by carboxylate anions and Cs + cations, respectively, leaving a long alkyl chain outside the surface for further protection against the ambient environment. 88 Zhou et al employed an anionic additive, TDCA, containing two carboxyl and a thiophene, which strengthened the coordination bonds with Pb 2+ due to the donation of electron pairs from S in the thiophene groups. 89…”
Section: Defect Passivationmentioning
confidence: 99%
“…[ 19 ] Hu et al reported that phenylbenzimidazole sulfonic acid (PBSA) additive led to the passivation treatment of the unreacted Pb 2+ defect through the strong interaction between SO on the PBSA sulfonic acid group and Pb 2+ , which significantly increased V OC from 1.09 to 1.16 V. [ 20 ] In short, the Lewis base molecule of SO binds well to Pb 2+ , passivating positively charged defects but having no effect on negatively charged defects. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…molecule of S═O binds well to Pb 2þ , passivating positively charged defects but having no effect on negatively charged defects. [21] Compared to Lewis bases, organic anions with appropriate size and multifunctional groups can further enhance the development potential. [22] According to the studies, [23] Zwitterionic molecules, with their possession of both positively and negatively charged functional groups in one molecular structure, are engaged in the passivation of both types of charged defects simultaneously.…”
Section: Introductionmentioning
confidence: 99%